Adolescent acquired thrombotic thrombocytopenic purpura: An analysis of the Pediatric Health Information System database. Issue 222 (February 2023) - Cohen, Clay T.; Zobeck, Mark; Kim, Taylor O.; Sartain, Sarah E.; Raffini, Leslie; Srivaths, Lakshmi
Abstract: The outcomes and characteristics of acquired thrombotic thrombocytopenic purpura (TTP) in adolescents is poorly understood due to an absence of studies focused on this population. To better understand the life-threatening disorder in this age, we performed an analysis of adolescent patients (ages 10–21) with TTP in the Pediatric Health Information Systems database from 2009 to 2020. The primary outcomes evaluated were in-hospital mortality and rate of TTP relapse. Secondary outcomes included rates of hemorrhagic and thrombotic complications during hospitalizations for TTP. Patients were included if they had a thrombotic microangiopathy diagnostic code, ADAMTS13 lab obtained, and received therapeutic plasmapheresis. Patients that received treatment for other non-TTP microangiopathies were excluded. A total of 99 patients with 123 hospitalizations for TTP treatment were identified. In-patient mortality occurred in 6 % ( n  = 6) and TTP relapse in 20 % ( n  = 20) of the cohort. Median time from initial admission to relapse was 33 days (IQR 15, 92). A hemorrhagic complication was identified in 29 % ( n  = 36) and thrombotic complication in 15 % ( n  = 19) of the cohort. The presence of underlying comorbidities was not associated with TTP relapse and only a diagnosis of cancer was associated with increased mortality. The rate of mortality and relapse in adolescent TTP is lower than that seen in adult registries. Long term prospective studies are needed to understand the long-term consequences of adolescent onset acquired TTP.